Regulation of an essential innate immune response by the p50 subunit of NF-kappaB. - Bohuslav, J (1998)
Recognition of bacterial endotoxin (LPS) elicits multiple host responses, including activation of cells of the innate immune system. LPS exposure occurs repeatedly during septicemia, making strict regulation of gene expression necessary. Such regulation might prevent, for example, the continuous production of proinflammatory cytokines such as tumor necrosis factor (TNF), which could lead to severe vascular collapse. Tolerance to LPS is characterized by a diminished production of TNF during prolonged exposure to LPS, and is therefore likely to represent an essential control mechanism during sepsis. In the present study, which uses mice with genetic deletions of the proteins of NF-kappaB complex, we provide data demonstrating that increased expression of the p50 subunit of NF-kappaB directly results in the downregulation of LPS-induced TNF production. This contention is supported by the following observations: (1) tolerance to LPS is not induced in macrophages from p50-/- mice; (2) long-term pretreatment with LPS does not block synthesis of TNF mRNA in p50-/- macrophages (in contrast to wild-type macrophages); (3) ectopic overexpression of p50 reduces transcriptional activation of the murine TNF promoter; and (4) analysis of the four kappaB sites from the murine TNF promoter demonstrates that binding of p50 homodimers to the positively acting kappaB3 element is associated with development of the LPS-tolerant phenotype. Thus, p50 expression plays a key role in the development of LPS tolerance.